(untitled) (International Journal of Physiotherapy, 2015)
Background: Flatfoot may exist as an isolated pathology or as part of a larger clinical entity. These entities include generalized ligamentous laxity, neurologic and muscular abnormalities, genetic conditions, collagen disorders and structural disorder. Flat foot is found to be associated with pronated foot. The objective of the study is to compare the effectiveness of foot taping versus custom-made medial arch support on pronated flatfoot in school going children. Methods: 60 students out of 130, aged 10 to 12 years were selected on the basis of inclusion criteria and divided into three groups from two different higher secondary schools at Srikalahasti, in Chittoor district, Andhra Pradesh. Group-A received custom-made medial arch support and foot strengthening exercises, Group-B received kinesio taping and foot strengthening exercises , Group-C received foot strengthening exercises for 4 weeks. The values of navicular drop test were taken after 4 weeks of study. The pre and post-test values were compared and results were tabulated. Results: All three groups showed significant improvement in navicular drop separately. No significant difference was found in the post-test values of group-A, group-B, group-C (p>0.05). However, the reduction of navicular drop was slightly more in group-B subjects treated with kinesio tape and foot strengthening exercises when compared with other two interventions. Conclusion: The study concluded that foot taping, custom-made medial arch support and foot strengthening exercises were found to be effective on pronated flatfoot in school going children aged 10 to 12 years.